Mathematical Modeling of Artificial Kidney Function By Using Blood Samples In Patients With Renal Diseases - Zainab Ismail; Sumia Hamad (Engineering and Technology Journal, 2010)
In Hemdialysis ,blood is pumped from the body to special filter (dialyzer ) madeof tiny plastic capillaries . the blood is purified when the waste products diffuse fromthe blood across the membrane of these tiny capillaries to the dialysate purified“clean”blood is then returned to the body and spent dialysate is drained.The purpose of this study is demonstrate the effect of increase nominal dialysateflow rate from 500-800 ml/min on the amount of the small solute (urea) removed fromthe blood and examine its effect on the amount of dialysis deliverd.Hemdialysis (HD) is a technique of removing or clearing solutes from theblood and removal of extra fluid from the body, by using dialyzing machine. Theprinciple of hemodialysis is primarily, the diffusion of solutes and ultrafiltration forremoval of extra fluid. Kinetic modeling is a widely used analytic process thatdescribes a system from its mass balance the clinical goals of modeling in dialysistherapy are to improve clinical understanding of the uremic syndrome and quantifieddoses of dialysis . In this study, we are interested for new model emerges formgeneralization of signal–pool urea kinetic model (variable volume single pool VVSP)which able to yield an accurate estimate of urea kinetic model such as urea nitrogengeneration rate, urea removal during dialysis and dialyzer urea clearance forquantifying and prescribing dialysis. The mathematical development of the variablevolume single pool ( VVSP) model for application is based primarily on the threeblood samples. This development provides a method to combine all of the treatmentparameters (Vt,PCR,G),urea is unique among the possible markers in providinginformation regarding a patients nitrogen balance . Urea concentration is directlyrelated to the protein catabolic rate blood urea concentrations reflected the balancebetween protein catabolism and clearance. We present the results obtained form aclinical study carried out on a group of 12 end stage renal disease (ESRD) patients forblood flow rate less than 200ml/min and greater than 200ml/min, 6 patients withdialysate flow rate (DFR) 500 ml/min and 6 patients with DFR 800 ml/min to showthe different in variable volume single pool (VVSP ) models for both groups (500 &800 ml/min) this method done typically in patients treated with HD twice-weekly so astandard modeling techniques include a standard blood urea nitrogen (BUN) sampleswhich are drawn before the beginning of HD, after the end of HD, and before thebeginning of the next HD and considering that volume changes occurring over the dialysis cycle this is the key idea that underlies the variable volume single-pool(VVSP)model.